Multilingualism, modern metropolis and youth: a sociolinguistic profile of a section of students of Calcutta University (Dhaka University Journal of Linguistics, 2010)
Kolkata has been a multilingual city for several hundredyears and like all modern metropolis it is home to diverse linguistic communities. Such multilingual metropolis almost always impacts the lives, the culture and languages of inhabitants. This is even more interesting when the communities in question are not a ‘native' community but are migrated. This paper tries to investigate the nature of its impact on the language use of a section of Calcutta University students whose native language is not Bengali. Through a questionnaire-based survey, we try to explore the pattern of language use of these students. Through this study we would like to show the model of language dynamics as exists among a section of youth in Kolkata, who are not speakers of the principle regional language, and indicate its effect on languages, individuals and communities concerned. Key words: multilingualism, urban sociolinguistics, language use, language maintenance and shift. DOI: 10.3329/dujl.v2i3.4140 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 1-18